Social Segregation and Educational Attainment Inequality in Argentina - Krüger, Natalia (Education Policy Analysis Archives, 2013)
This paper analyzes the impact of high school socioeconomic segregation on educational equity in Argentina. The presence of segregation means that students are unevenly distributed throughout the system, concentrating in certain schools according to their social origin. The aim is to assess whether this process can increase educational attainment inequality. Using the PISA 2009 database, multilevel models are estimated in order to examine the effects of schools` social composition on individual reading performance. The evidence supports the existence of significant compositional effects which help explain test score dispersion. This suggests that young people of low socioeconomic status face a double educational risk: i) an initial disadvantage related to their social and family background; and ii) a high probability of assisting a school with a vulnerable student population, where they may be exposed to negative peer effects. The findings support the need to consider the social composition of schools as a key educational policy factor, and the relevance of analyzing ways to promote social inclusion in the system.